Application of thiourea modified charcoal adsorbent in adsorbing ciprofloxacin

Through the preparation of thiourea modified biochar adsorbent, the problem of ciprofloxacin removal in water bodies was solved, and efficient and green adsorption effect was achieved, which significantly improved the removal rate and adsorption capacity of ciprofloxacin.

CN119461559APending Publication Date: 2025-02-18CHANGZHOU UNIV

Patent Information

Application Number
CN202411588453.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove ciprofloxacin from water bodies, and the traditional methods are expensive, inefficient and non-green.

Method used

Using thiourea modified biochar adsorbent, the thiourea modified biochar adsorbent with high specific surface area and rich functional groups is prepared for adsorption by mixing rice straw powder with thiourea and sodium carbonate and pyrolyzing treatment. Ciprofloxacin.

Benefits of technology

The adsorption performance of ciprofloxacin was significantly improved, with the maximum adsorption capacity reaching 444.8 mg/g and the removal rate reached 99.7%, which was significantly improved compared with the maximum adsorption amount and removal rate of the original biochar.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461559A_ABST
    Figure CN119461559A_ABST
Patent Text Reader

Abstract

The invention discloses an application of a thiourea modified charcoal adsorbent in adsorption of ciprofloxacin. The preparation method comprises the following steps: grinding and uniformly mixing rice straw powder, thiourea and sodium carbonate, pyrolyzing in inert gas, cooling, grinding and sieving to obtain a biochar material; and washing, carrying out suction filtration and drying to obtain the thiourea modified charcoal adsorbent. The thiourea modified biochar adsorbent is used for carrying out an adsorption experiment on 50 mg / L of CIP, the maximum adsorption capacity of the thiourea modified biochar adsorbent on the CIP is 444.8 mg / g after 60 minutes, the removal rate of the CIP reaches 99.7% when adsorption is balanced, excellent adsorption performance is shown, and the thiourea modified biochar adsorbent can be used as a good adsorbent for controlling ciprofloxacin pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental functional materials and biomass resource utilization, and particularly relates to application of a thiourea-modified biochar adsorbent in adsorbing ciprofloxacin. Background Art

[0002] In recent years, due to the extensive use of medicines and care products in people's daily lives, more and more metabolites are released into the aquatic environment through various means such as flushing, urine and feces. Ciprofloxacin is a fluoroquinolone antibiotic that is widely used to treat human and animal diseases. However, due to the widespread use and discharge of CIP, its presence in water bodies has attracted people's attention. The contamination of ciprofloxacin may pose risks to the environment and organisms, especially posing potential hazards to aquatic organisms and humans. Due to the presence of fluoride ions in the structure of CIP, CIP is highly stable and difficult to degrade, so it is a great challenge to remove CIP from wastewater.

[0003] Currently proposed methods for removing CIP from wastewater include membrane separation, ozonation, photodegradation, and electro-Fenton, but these methods have been proven to be expensive, inefficient, and non-green.

[0004] Biochar is an excellent adsorption material with a wide range of sources, simple production and environmental protection. Many agricultural and forestry wastes can be modified by high-temperature pyrolysis to produce a porous structure with high specific surface area and high efficiency. Its developed adsorption properties can be used to remove organic dyes, antibiotics in water and heavy metal ions.

[0005] At present, most modified biochars have low adsorption selectivity and are difficult to adsorb antibiotics. After a long period of adsorption, they reach saturation and need to be updated. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide an application of a thiourea-modified biochar adsorbent in the adsorption of ciprofloxacin. The thiourea-modified biochar adsorbent of the present invention exhibits excellent adsorption performance for ciprofloxacin and can be used as a good adsorbent for CIP pollution control.

[0007] Technical solution: The purpose of the present invention is achieved through the following technical solution:

[0008] The present invention provides an application of a thiourea-modified biochar adsorbent in adsorbing ciprofloxacin. The preparation method of the thiourea-modified biochar adsorbent comprises the following steps:

[0009] (1) grinding and uniformly mixing rice straw powder, thiourea and sodium carbonate to obtain a mixture;

[0010] The mass ratio of the rice straw powder to thiourea is 1-2:2-1;

[0011] The mass ratio of thiourea to sodium carbonate is 1-2:2-1;

[0012] (2) pyrolyzing the mixture obtained in step (1) under an inert gas, and then grinding and sieving to obtain a biochar material;

[0013] (3) Washing, filtering and drying the biochar material obtained in step (2) to obtain the thiourea-modified biochar adsorbent.

[0014] The present invention adopts rice straw powder as biomass to synthesize thiourea modified biochar. Thiourea has N and S double functional groups, which changes the chemical properties of its surface, increases the surface active sites, can effectively reduce the adsorption of other organic matter, and improve the adsorption effect.

[0015] In step (1), the rice straw powder is obtained by drying the rice straw to a constant weight, sieving and then grinding; the drying temperature is 85-120° C., and the time is 2-3 hours; and the mesh size of the sieving is 100 meshes.

[0016] In step (2), the inert gas is nitrogen, and the flow rate of the nitrogen is controlled at 60 to 80 mL / min.

[0017] In step (2), the pyrolysis is carried out at a heating rate of 7-10°C / min to 600-900°C, and the pyrolysis is carried out at this temperature for 1-3h.

[0018] In step (2), the mesh size of the sieving is 100 meshes.

[0019] In step (3), the washing method is washing with anhydrous ethanol and ultrapure water; the drying temperature is 85 to 120° C., and the drying time is 12 to 20 hours.

[0020] The added amount of the thiourea modified biochar adsorbent is 0.2-0.7 g / L; the concentration of ciprofloxacin is 20-160 mg / L.

[0021] The present invention also provides a method for removing ciprofloxacin from water, wherein a thiourea-modified biochar adsorbent is added to the water, wherein the thiourea-modified biochar adsorbent is prepared by the following method:

[0022] (1) drying rice straw at 95° C. for 2 h, grinding the rice straw into powder, and passing the powder through a 100-mesh sieve to obtain rice straw powder;

[0023] (2) The rice straw powder obtained in step (1) was mixed with thiourea in a mass ratio of 2:1, and thiourea and anhydrous sodium carbonate in a mass ratio of 1:2, with a nitrogen flow rate of 70 mL / min, and the temperature was raised to 800°C at a rate of 10°C / min, and kept at this temperature for 2 h, cooled, and then ground and sieved to obtain a biochar material;

[0024] (3) washing the biochar material obtained in step (2) with anhydrous ethanol and ultrapure water for three times, drying at 100° C. for 15 h to obtain a thiourea-modified biochar adsorbent, and sealing and storing the mixture;

[0025] The added amount of the thiourea modified biochar adsorbent is 0.2-0.7 g / L.

[0026] The present invention prepares rice straw powder into biochar for use. The biochar has a series of functional structures. However, since the original biochar has a small specific surface area and low porosity, thiourea is used to modify the original biochar to increase the specific surface area and enrich the functional groups on the biochar, which can provide active sites for the reaction system and improve the removal ability of CIP.

[0027] Beneficial effects:

[0028] The present invention conducts an adsorption experiment on 50 mg / L CIP by using thiourea-modified biochar adsorbent and original biochar. After 60 minutes, the maximum adsorption capacity of CIP by the thiourea-modified biochar adsorbent is 444.8 mg / g, and the removal rate of CIP reaches 99.7% at adsorption equilibrium; the maximum adsorption capacity of ciprofloxacin by the original biochar is 126.6 mg / g, and the removal rate is as high as 63.1%. Therefore, compared with the prior art, the adsorption performance of the thiourea-modified biochar adsorbent of the present invention is significantly improved, and it has a good adsorption effect on CIP. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The SEM and SEM-Mapping images of the original rice straw biochar prepared in Example 1 of the present invention and the thiourea-modified biochar adsorbent prepared in Example 2;

[0030] Figure 2 XRD patterns of the original rice straw biochar prepared in Example 1 and the thiourea-modified biochar adsorbent prepared in Example 2;

[0031] Figure 3 FTIR spectra of the original rice straw biochar prepared in Example 1 and the thiourea-modified biochar adsorbent prepared in Example 2;

[0032] Figure 4 Adsorption isotherm of CIP by thiourea-modified biochar adsorbent prepared in Example 2

[0033] Figure 5 This is the cycle performance diagram of the thiourea modified biochar adsorbent material prepared in Example 2. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is described in detail below through specific embodiments, but the protection scope of the present invention is not limited to the embodiments.

[0035] The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are commercially available products unless otherwise specified.

[0036] The rice straw used in the experiment was collected from farmland straw in Huangli Town, Wujin District, Changzhou City.

[0037] The CIP concentration prepared in the experiment was 20-160 mg / L, and the adsorbent dosage was 0.4 g / L.

[0038] Example 1 Preparation of raw rice straw biochar

[0039] (1) drying the rice straw in a drying oven to remove most of the moisture at 95° C. for 2 h, grinding the dried rice straw into powder by mechanical crushing, and filtering through a 100-mesh sieve to obtain rice straw powder;

[0040] (2) The rice straw powder obtained in step (1) was pyrolyzed in a N2 atmosphere at a N2 flow rate of 70 mL / min, and the temperature was raised to 800°C at a rate of 10°C / min, and kept at this temperature for 2 h. After cooling, it was ground and sieved to obtain the original biochar material (denoted as "800").

[0041] Example 2 Preparation of thiourea modified biochar adsorbent

[0042] (1) drying the rice straw in a drying oven to remove most of the moisture at 95° C. for 2 h, grinding the dried rice straw into powder by mechanical crushing, and filtering through a 100-mesh sieve to obtain rice straw powder;

[0043] (2) The rice straw powder obtained in step (1) was mixed with thiourea in a mass ratio of 2:1, and thiourea and anhydrous sodium carbonate in a mass ratio of 1:2, with a nitrogen flow rate of 70 mL / min, and the temperature was raised to 800°C at a rate of 10°C / min, and kept at this temperature for 2 h, cooled, and then ground and sieved to obtain a biochar material;

[0044] (3) The biochar material obtained in step (2) was washed three times with anhydrous ethanol and ultrapure water, and dried at 100° C. for 15 h to obtain a thiourea-modified biochar adsorbent (denoted as “NS-800”) which was sealed and stored.

[0045] The SEM and SEM-Mapping images of the original rice straw biochar prepared in Example 1 and the thiourea-modified biochar adsorbent prepared in Example 2 are shown in Figure 1 .

[0046] Figure 1 (a) is the original biochar at 800℃, with fewer surface pores and composed of many irregularly shaped fragments, which mainly come from the thermal decomposition of cellulose and hemicellulose. After thiourea modification in Figure (b), many uneven spherical particles appeared on the surface. These spherical particles may be introduced after thiourea modification. The N source and S source are attached to the surface of the biochar, which increases its specific surface area and produces some larger pores. As shown in Figure (c), Figure (d), Figure (e), and Figure (f), they represent the mapping maps of C, O, N, and S, respectively. This also confirms that the surface of the biochar modified by thiourea has attached materials, which are evenly distributed on the surface of the biochar. According to the element distribution, the biochar modification is successful. The results show that the biochar modified by thiourea has a larger specific surface area and pore volume, thereby improving the adsorption efficiency.

[0047] The XRD spectra of the original rice straw biochar prepared in Example 1 (marked as "800" in the figure) and the thiourea modified biochar adsorbent prepared in Example 2 (marked as "NS-800" in the figure) are shown in Figure 2 .

[0048] The internal structure of the crystal is one of the important factors to judge the adsorption performance of the material. The crystal structure of the original rice straw biochar "800" and NS-800 biochar was detected by X-ray diffractometer (XRD). Figure 2 As shown in the figure, the biochar has diffraction peaks belonging to cellulose and wood trees at 2θ = 15.7° and 22.9°, and the biochar modified with thiourea has diffraction peaks at 2θ = 24.4° and 44.5°, which correspond to the (002) crystal plane and (100) crystal plane of graphitized carbon. This shows that the cellulose and lignin in the rice straw raw material have been thermally decomposed and converted into a biochar material with a carbon structure as the main component. By comparison, it can be seen that the peak at 2θ = 44.5° becomes stronger after adding thiourea modification, indicating that the degree of crystallization becomes higher and the adsorption performance is improved.

[0049] The FTIR spectra of the original rice straw biochar prepared in Example 1 (marked as "800" in the figure) and the thiourea modified biochar adsorbent prepared in Example 2 (marked as "NS-800" in the figure) are shown in FIG. Figure 3 .

[0050] The surface functional groups of the original rice straw biochar "800" and NS-800 were analyzed by FTIR spectra. Most of the absorption peaks of the two biochars appeared in roughly the same position. The results are as follows Figure 3 As shown, at 3443.8cm -1 The peak at 2848.8 cm corresponds to the stretching vibration of the -OH functional group; -1 The peak at 2587.6 cm -1 The peak at 1562.8 cm represents the stretching vibration of the SH functional group; -1 The peak at 1376.6 cm corresponds to the stretching vibration of the C=N functional group; -1 The peak at 1084.8cm corresponds to the peak of the N group. Since NS-800 is a biochar modified by thiourea, a large amount of N source is introduced. Therefore, the vibration intensity of "NS-800" is stronger than that of "800" biochar, indicating that the modifier is successfully typed into the carbon structure framework. -1 The peak at 844.4 cm-1 represents the stretching vibration of the CO functional group; the peak at 838.3 cm-1 belongs to the stretching vibration peak of the CS functional group.

[0051] The method for investigating the adsorption performance of simulated pollutants provided by the present invention is as follows:

[0052] Adsorption test:

[0053] Weigh 0.1g of ciprofloxacin and place it in a 500ml beaker, add pure water to dilute to the mark, stir and dissolve to prepare a 200mg / L ciprofloxacin stock solution. Add 5mg of adsorbent into 40mL, 50mg / L ciprofloxacin solution for adsorption experiment. Oscillate at 180rpm at 25℃, take out 1mL of solution at 5, 10, 15, 20, 30, 40 and 60min, filter with 0.45um filter membrane immediately after taking out, and measure the ciprofloxacin concentration at 275nm with ultraviolet spectrophotometer. All experiments were carried out in parallel 3 times, and blank controls were carried out simultaneously.

[0054] When performing concentration measurements using a UV spectrophotometer, the Beer-Lambert law is applied to calculate the concentration of the sample.

[0055] The Beer-Lambert law formula is as follows:

[0056] A=ε·C·l

[0057] in,

[0058] A: Absorbance (dimensionless)

[0059] ε: Molar absorptivity (L·mol-1·cm-1), which indicates the absorptivity of a solute at a specific wavelength

[0060] C: concentration (mol / L or g / L), concentration of solute

[0061] l: Optical path length (cm), usually the thickness of the cuvette.

[0062] Mathematical model of adsorption kinetics

[0063] The expression of pseudo-first-order kinetics is:

[0064] ln(q e -q t )=lnq e -k1t

[0065] The expression of pseudo-second-order kinetics is:

[0066]

[0067] Where: q t —Unit adsorption capacity at time t (mg / g);

[0068] q e —Unit adsorption capacity at equilibrium (mg / g);

[0069] The adsorption isotherm of CIP by the thiourea modified biochar adsorbent prepared in Example 2 is shown in Figure 4 , isothermal adsorption model parameters are shown in Table 1:

[0070] Table 1 Isotherm adsorption model parameters

[0071]

[0072] According to the fitting results ( Figure 4 , Table 1), we can know the correlation coefficient R of the Langmuir isotherm adsorption model 2 The correlation coefficient R of the Freundlich isotherm adsorption model is 0.9998, which is higher than that of the Freundlich isotherm adsorption model. 2 is 0.9716. This shows that the Langmuir model is more in line with the actual situation, and the adsorption behavior of the adsorbent material on CIP is mainly monolayer adsorption. The adsorption force index 1 / n in the Freundlich model is 0.3841, which is between 0.1 and 0.5, which proves that the adsorbent material is easy to react with CIP. K F The value is 56.9, K F The larger the value, the better the adsorption performance of the biochar, while the smaller the 1 / n value, the stronger the adsorption intensity.

[0073] The cycle performance diagram of the thiourea modified biochar adsorbent material prepared in Example 2 is shown in Figure 5 .

[0074] The recycling of adsorbents is a key indicator for evaluating the practicality and environmental friendliness of adsorbents. This study evaluated the recycling performance of "NS-800". The experimental results are as follows Figure 5 As shown, the CIP concentration is 50 mg / L and the adsorbent dosage is 0.4 g / L.

[0075] After five cycles of testing, the removal rate of CIP by "NS-800" remained above 70%, indicating that the above-mentioned thiourea-modified biochar can maintain relatively stable performance during the adsorption process, and there is no significant decrease in the removal rate. This also confirms that the material has good recycling performance and provides strong evidence for the treatment of actual sewage.

[0076] The maximum adsorption capacity of the thiourea-modified biochar adsorbent prepared in Example 2 after 60 minutes was 444.8 mg / g, and the removal rate of CIP reached 99.7%.

[0077] Example 3

[0078] Referring to the preparation method of Example 2, the mass ratio of rice straw powder to thiourea in step (2) of Example 2 was adjusted to 1:1, and the other conditions were the same as those of Example 2. This was to explore the effect of different mass ratios of thiourea-modified biochar materials on the adsorption of CIP. The experimental results showed that the removal rate of CIP by the thiourea-modified biochar prepared under these conditions reached a maximum of 87.2%, and the maximum adsorption capacity was 376.8 mg / g.

[0079] Example 4

[0080] Referring to the preparation method of Example 2, the mass ratio of rice straw powder to thiourea in step (2) of Example 2 was adjusted to 1:2, and the other conditions were the same as those of Example 2. This was to explore the effect of different mass ratios of thiourea-modified biochar materials on the adsorption of CIP. The experimental results showed that the removal rate of CIP by the thiourea-modified biochar prepared under these conditions reached a maximum of 85.6%, and the maximum adsorption capacity was 336.7 mg / g.

[0081] Example 5

[0082] Referring to the preparation method of Example 2, the mass ratio of thiourea to anhydrous sodium carbonate in step (2) of Example 2 was adjusted to 1:1, and the other conditions were the same as those of Example 2. This was to explore the effect of different mass ratios of thiourea-modified biochar materials on the adsorption of CIP. The experimental results showed that the removal rate of CIP by the thiourea-modified biochar prepared under these conditions reached up to 92.1%, and the maximum adsorption capacity was 392.5 mg / g.

[0083] Example 6

[0084] Referring to the preparation method of Example 2, the mass ratio of thiourea to anhydrous sodium carbonate in step (2) of Example 2 was adjusted to 2:1, and the other conditions were the same as those of Example 2. The effect of different mass ratios of thiourea-modified biochar materials on the adsorption of CIP was explored. The experimental results show that the removal rate of CIP by the thiourea-modified biochar prepared under these conditions is as high as 86.4%, and the adsorption capacity is as high as 349.2 mg / g.

[0085] Example 7

[0086] Referring to the preparation method of Example 2, the only difference from Example 2 is that in step (2), the nitrogen flow rate is 65 mL / min and the heating rate is 10°C / min; other conditions are the same as in Example 2, and a thiourea-modified biochar adsorbent material is obtained.

[0087] The adsorption experiment method was the same as that in Example 2, and the removal rate of ciprofloxacin reached a maximum of 92.4%, and the adsorption amount was 406.8 mg / g.

[0088] Example 8

[0089] Referring to the preparation method of Example 2, the only difference from Example 2 is that the pyrolysis temperature in step (2) is set to 700°C and the heating rate is 10°C / min; other conditions are the same as in Example 2, and a thiourea-modified biochar adsorbent material is obtained.

[0090] The adsorption experiment method was the same as that in Example 2, and the removal rate of ciprofloxacin reached a maximum of 89.9%, and the adsorption amount was 395.6 mg / g.

[0091] The adsorbent of the present invention has a good adsorption effect on ciprofloxacin. In addition, it can be seen from the experimental data of the embodiment that the adsorbent prepared under different conditions is subjected to the adsorption experiment of ciprofloxacin, and the adsorption capacity and removal rate obtained are different. Therefore, it is particularly important to select suitable materials for the adsorption of ciprofloxacin.

[0092] Comparative Example 1

[0093] The original biochar "800" prepared in Example 1 was used to adsorb ciprofloxacin. The dosage of the original biochar adsorbent was 5 mg, and the concentrations of ciprofloxacin were 40 mL and 50 mg / L. The test showed that the highest removal rate of ciprofloxacin by "800" was 63.1%, and the maximum adsorption capacity after 60 minutes was 126.6 mg / g.

[0094] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention as defined in the appended claims.

Claims

1. Application of a thiourea-modified biochar adsorbent in the adsorption of ciprofloxacin, characterized in that: The preparation method of the thiourea modified biochar adsorbent comprises the following steps: (1) grinding and uniformly mixing rice straw powder, thiourea and sodium carbonate to obtain a mixture; The mass ratio of the rice straw powder to thiourea is 1-2:2-1; The mass ratio of thiourea to sodium carbonate is 1-2:2-1; (2) pyrolyzing the mixture obtained in step (1) under an inert gas, cooling it, and then grinding and sieving it to obtain a biochar material; (3) Washing, filtering and drying the biochar material obtained in step (2) to obtain the thiourea-modified biochar adsorbent.

2. The use according to claim 1, characterized in that: In step (1), the rice straw powder is obtained by drying the rice straw to a constant weight, sieving and then grinding; the drying temperature is 85-120° C., and the time is 2-3 hours; and the mesh size of the sieving is 100 meshes.

3. The use according to claim 1, characterized in that: In step (2), the inert gas is nitrogen, and the flow rate of the nitrogen is controlled at 60 to 80 mL / min.

4. The use according to claim 1, characterized in that: In step (2), the pyrolysis is carried out at a heating rate of 7-10°C / min to 600-900°C, and the pyrolysis is carried out at this temperature for 1-3h.

5. The use according to claim 1, characterized in that: In step (2), the mesh size of the sieving is 100 meshes.

6. The use according to claim 1, characterized in that: In step (3), the washing method is washing with anhydrous ethanol and ultrapure water; the drying temperature is 85 to 120° C., and the drying time is 12 to 20 hours.

7. The use according to claim 1, characterized in that: The added amount of the thiourea modified biochar adsorbent is 0.2-0.7 g / L; the concentration of ciprofloxacin is 20-160 mg / L.

8. A method for removing ciprofloxacin from water, characterized in that: Adding a thiourea-modified biochar adsorbent to a water body, wherein the thiourea-modified biochar adsorbent is prepared by the following method: (1) drying rice straw at 95° C. for 2 h, grinding the rice straw into powder, and passing the powder through a 100-mesh sieve to obtain rice straw powder; (2) The rice straw powder obtained in step (1) was mixed with thiourea in a mass ratio of 2:1, and thiourea and anhydrous sodium carbonate in a mass ratio of 1:2, with a nitrogen flow rate of 70 mL / min, and the temperature was raised to 800°C at a rate of 10°C / min, and kept at this temperature for 2 h, cooled, and then ground and sieved to obtain a biochar material; (3) washing the biochar material obtained in step (2) with anhydrous ethanol and ultrapure water for three times, drying at 100° C. for 15 h to obtain a thiourea-modified biochar adsorbent, and sealing and storing the mixture; The added amount of the thiourea modified biochar adsorbent is 0.2-0.7 g / L.

Citation Information

Patent Citations

  • Preparation method and application of nitrogen-sulfur co-doped biochar

    CN110237818A

  • Method for adsorbing antibiotics in water by using silver-ytterbium modified biochar

    CN113457623A

  • Magnetic sulfur-nitrogen-doped biochar composite material, preparation method thereof and application of magnetic sulfur-nitrogen-doped biochar composite material in co-adsorption of antibiotics and heavy metal ions

    CN115501858A

  • Nitrogen and sulfur co-doped modified biochar material and application thereof

    CN115990502A

  • Carbon Composite, and Preparation Method and Use Thereof

    US20240262696A1

Cited By

  • Preparation method of modified sunflower seed shell biochar adsorbent, adsorbent and application thereof

    CN122377429A